Penguatan Perilaku Toleransi dalam Pembelajaran IPS di SMP Pangudi Luhur Salatiga - Riyanto, Bagja; Lestari, Puji (Sosiolium: Jurnal Pembelajaran IPS, 2020)
SMP Pangudi Luhur Salatiga is one of the schools that has illustrated diversity, in terms of religion, ethnicity, socio-economy, and gender/gender. This article aims to 1) explain the strengthening of tolerance behavior in social studies learning at SMP Pangudi Luhur Salatiga. 2) Knowing the driving and inhibiting factors in strengthening tolerance behavior in social studies learning at SMP Pangudi Luhur Salatiga. The results of this study found that 1) Strengthening can be carried out in the planning stage through integrating the RPP; Implementation through a number of stimuli so that students become accustomed (response) to tolerant behavior (initial, core, and closing; Evaluation in the form of journals that have been made by the teacher. God, humble, good role model, loving others, wise, soft-hearted and enthusiastic and determined. 2) The driving factors include the school environment, learning materials, learning methods, awareness, and frequency, while the inhibiting factors are teachers lack of training, poor conditions. suspect, supervision, and facilities/infrastructure.